Design considerations for charge‐compensated fast‐switching power MOSFET in the medium‐voltage range. Issue 4 (1st April 2018) - Siemieniec, Ralf; Braz, Cesar; Blank, Oliver
Abstract : Low‐voltage power metal–oxide–semiconductor field‐effect transistors (MOSFETs) based on charge compensation using a field plate offer a significant reduction of the area‐specific on‐resistance. The extension of their blocking capability into the so‐called medium‐voltage range of 150–300 V promises devices with excellent properties being attractive for a wide range of applications. There are two approaches how this voltage‐range extension can be realised. Both concepts are linked to different device performance and different development effort. This study discusses both concepts using the example of the 150 V device class and compares the performance gained at the device and application level.